Structure of organoruthenium-derived Langmuir monolayers at the air-water interface: A molecular-modelling approach - Costello, J; Davies, S; Highcock, R; Polywka, M; Poulter, M; Richardson, T; Roberts, G (1997)
A two-dimensional model for the structure of films fabricated from organoruthenium amphiphiles of the type [Ru(η5-C5H5)(PPh2R) 2(p-NCC6H4OR′)]PF6 (R = Ph,p-tolyl or p-biphenyl; R′ = Et or C16H33) at the air-water interface has been devised.